Fibre-optic measurement of strain and shape on a helicopter rotor blade during a ground run: 1. Measurement of strain - James, Stephen W.; Kissinger, Thomas; Weber, Simone; Mullaney, Kevin; Chehura, Edmond (IOP Publishing, 2022)
Optical fibre strain and shape measurement sensors were deployed on a 5-m long rotor blade during a full-speed (rotation rate 6.6 Hz) helicopter ground run, with real-time data wirelessly streamed from rotor hub-mounted sensor interrogators. In Part 1 of a 2-part paper series, the strain sensing capabilities of the two optical fibre-based sensing techniques, optical fibre Bragg grating (FBG) and fibre segment interferometry (FSI), are compared, while Part 2 (Kissinger et al 2022 Smart Mater. Struct. accepted) specifically investigates the blade shape measurement based on the FSI approach. In part 1, the rotor hub-mounted instrumentation is described, and data on the dynamics of the blade obtained from a sequence of controlled pilot inputs are analysed both in the time and spectral domains. It is shown that this can provide insights into the aeroelastic properties of the blade. Noise standard deviations of 0.2 n√ ε/ Hz and 30 nε/ Hz for the FSI and FBG-based sensing approaches, respectively, were observed over a strain range of 3500 µepsilon.